1985
DOI: 10.2527/jas1985.611179x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Particle Size and Feeding of H2-Receptor Antagonists on Gastric Ulcers in Swine1

Abstract: Four experiments were conducted to evaluate the effect of diet and the administration of H2-antagonists in feed on gastric ulcer formation and performance of growing-finishing swine. Pigs receiving a finely ground diet (less than lmm) grew faster (.73 vs .68 kg/d, P less than .01) and had better feed utilization (3.47 vs 3.76, P less than .01) than pigs receiving a cracked corn-based diet. Incidence of ulcers in the esophageal region of the stomach of pigs fed the finely ground diet was greater (P less than .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 4 publications
(7 reference statements)
1
16
1
2
Order By: Relevance
“…Those pigs that had no ulcers at slaughter grew faster than those pigs with a score of 1 (P < 0.05) (0.98 vs. 0.84 kg d -1 ), with a tendency (P < 0.01) for a lower ADG for all pigs with ulcer scores. This supports work done by Hedde et al (1985), who found that an increase in ulcer severity was associated with a marked reduction in growth performance. It has been suggested that only pigs with a severe gastric ulcer will have a depressed growth rate, probably due to gastric hemorrhage.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Those pigs that had no ulcers at slaughter grew faster than those pigs with a score of 1 (P < 0.05) (0.98 vs. 0.84 kg d -1 ), with a tendency (P < 0.01) for a lower ADG for all pigs with ulcer scores. This supports work done by Hedde et al (1985), who found that an increase in ulcer severity was associated with a marked reduction in growth performance. It has been suggested that only pigs with a severe gastric ulcer will have a depressed growth rate, probably due to gastric hemorrhage.…”
Section: Resultssupporting
confidence: 80%
“…There was no difference in final endoscopic ulcer score due to dietary particle size. This is not in agreement with work done by Gamble et al (1967), Reimann et al (1968), Pickett et al (1969), Pocock et al (1969), Maxwell et al (1970), and Hedde et al (1985), who found that a smaller particle size (approximately 500-600 µm) increased both the severity and the incidence of gastric ulcers. A smaller particle size has been shown to increase the pepsin activity, decrease the pH in the esophageal region, reduce the pH gradient between the pars esophageal and pyloric regions, and increase the percent moisture and fluidity of the stomach contents (Maxwell et al 1972).…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Improved feed efficiency and digestibility of nutrients and energy were reported with fine grinding of major grains such as maize (Reimann et al, 1968;Hedde et al, 1985;Wondra et al, 1995), and sorghum (Owsley et al, 1981). But the optimum particle size is probably dependent on the age of pigs.…”
Section: Introductionmentioning
confidence: 99%